Identification, cloning and characterization of a novel Gossypium hirsutum L. GhMYBantiV transcription factor in response to biotic and abiotic stresses - Fei, Li; Xiaoyan, Chen; Xiaohong, He; Ming, Tang; Kun, Hong; Zhengting, Yang; Yin, Yi; Zhanji, Liu; Mingchuan, Fu (The Indian Journal of Genetics and Plant Breeding, 2017)
Verticillium wilt is an important worldwide limiting factor for cotton production. Improving cotton varieties’ disease resistance, is of great strategic and practical importance to promote world cotton production and to improve cotton fibre quality. Taking advantage of the Gossypium raimondii genome sequence, we cloned a new MYB transcription factor GhMYBantiV (GenBank accession number: KM0407832) from upland cotton variety Lumianyan 32. Characteristic analysis indicates that GhMYBantiV is a MYB transcription factor, since it localises in the nucleus, and shows the transcription factor activity. GhMYBantiV expression is greatly enhanced by Verticillium wilt fungus infection and salt treatment. It is, therefore, suggested that GhMYBantiV possibly plays an important role in biotic and abiotic stress response in cotton.